RESOURCE AMASSEMENT AS A TOOL OF MAXIMIZING SEA POWER IN THE INDIAN OCEAN - Ramla Khan (Andalas Journal of International Studies (AJIS), 2019)
The paper discusses the fundamentals behind the Indian Ocean as the new pivotal of the twenty-first century cauldron, bearing high-yielding economic driving potential analyzed from the sparsely deliberated Classical Realist vistas of Morgenthau that form an intertwine between accumulation of resources and maximization of power. The aim of paper is to provide new dimensions to the IOR rivalry between the power-players whose preponderance remains vital to the control of the sea resources. The present geopolitical settings embedded in the virtues of multifaceted interdependence would not allow for war to be denominated as an appropriate strategy to win the concentrated control of sea wealth. Indian Ocean residues abundant possessions vibrant for the sustenance of human society, economic upheavals and for the purpose of modernizing military capabilities. The Blue Economy approach is subject of discussion in the study offers a way-out, stipulating joint development of resources as the rational approach which would foster cooperation, stability of the Sea-Lines of Communications and smooth running of the economic engines. The proposed approach would provide benefits extending to major littoral and regional states including India, China and Pakistan but also to the foreign stakeholders in the form of United States and Europe.   Key words: Sea Power, Power Maximization, Resource Politics, Blue Economy